Phlebotomine sand flies (Diptera: Psychodidae) and sand fly-borne pathogens in the Greater Mekong Subregion: a systematic review - John Hustedt; Didot Budi Prasetyo; Jodi M. Fiorenzano; Michael E. von Fricken; Jeffrey C. Hertz (Parasites & Vectors, 2022)
Abstract Phlebotomine sand flies are proven or suspected vectors of several pathogens of importance, including leishmaniasis, bartonellosis and sand fly fevers. Although sand flies have a worldwide distribution, there has been limited research published on sand flies and sand fly-borne pathogens throughout the Greater Mekong Sub-region (GMS). This review followed the PRISMA guidelines to determine the biodiversity and presence of phlebotomine sand flies and their associated pathogens in the GMS, specifically Cambodia, Thailand, the Lao People’s Democratic Republic (Laos), Malaysia and Vietnam. A total of 1472 records were identified by searching electronic databases, scanning reference lists of articles and consulting experts in the field. After screening of title and abstracts, 178 records remained and were further screened for original data (n = 34), not having regional data (n = 14), duplication of data (n = 4), records not available (n = 4) and no language translation available (n = 2). A total of 120 studies were then included for full review, with 41 studies on sand fly-related disease in humans, 33 studies on sand fly-related disease in animals and 54 entomological studies focused on sand flies (5 papers contained data on > 1 category), with a majority of the overall data from Thailand. There were relatively few studies on each country, with the exception of Thailand, and the studies applied different methods to investigate sand flies and sand fly-borne diseases, impacting the ability to conduct meaningful meta-analysis. The findings suggest that leishmaniasis in humans and the presence of sand fly vectors have been reported across several GMS countries over the past 100 years, with local transmission in humans confirmed in Thailand and Vietnam. Additionally, local Mundinia species are likely transmitted by biting midges. Findings from this study provide a framework for future investigations to determine the geographic distribution and risk profiles of leishmaniasis and other associated sand fly-borne disease throughout the GMS. It is recommended that researchers expand surveillance efforts across the GMS, with an emphasis placed on entomological surveys, syndromic and asymptomatic monitoring in both humans and animals and molecular characterization of sand flies and sand fly-borne pathogens, particularly in the understudied countries of Cambodia, Vietnam and Laos. Graphical abstract